An Analysis of the Effect of Code Ownership on Software Quality across Windows, Eclipse, and Firefox - Gall, Harald; Devanbu, Premkumar; Murphy, Brendan; Bird, Christian; Nagappan, Nachi (2010)
Ownership is a key aspect of large-scale software development. We examine the relationship between different ownership measures and software faults/failures in three large software projects drawn from different process domains: Windows Vista, the Eclipse Java IDE, and the Firefox Web Browser. We find that in all cases, measures of ownership such as the number of low-expertise developers, and the proportion of ownership for the top owner have a relationship with both pre-release faults and post-release failures. However, we find that the strength of the effects is related to the development process used. Vista shows the strongest relationship with ownership level, followed by Eclipse, and then Firefox, suggesting that the more that a project uses an open source style process, the more that team sizes rather than ownership levels affect to failures. We also find reasons that low-expertise developers make changes to components and show that the removal of low-expertise contributions dramatically decreases the performance of contribution based defect prediction. Finally we provide recommendations for source code change policies and utilization of resources such as code inspections based on our results.